Índices físicos e recalque superficial de um Latossolo vermelho submetido a diferentes cargas e tipos de manejo - (:unkn) unknown (Universidade Estadual de Goiás, 2022)
The structural evaluation of an agricultural soil is extremely important for the performance and qualityof production. When submitted to the traffic of agricultural machines, the soils suffer a surfacerepression and change their physical characteristics according to the management in which they aresubmitted. Therefore, this work aimed to evaluate the physical indices and the surface settlement of ared oxisol subjected to different loads and types of management, so samples of undisturbed soil werecollected in three areas with different management systems, no-till, Crop Integration System LivestockForest and pasture area; then, a traffic simulator with dynamic load application 0 past, 1 past and 2past (0, 108 and 216 kpa) was submitted, evaluating the physical indices of the soil specific weight (γn),specific apparent dry weight (γd), index of voids (n) and porosity (e). Soon after, the samples weresubmitted to the uniaxial compression test to verify the surface settlement, with 5 loads (108, 216, 432,864 and 1500 Kpa). The experiment was carried out in a completely randomized design, with a 3x3x5factorial scheme in sub-subdivided plots. Thus, it was found that direct planting, due to themanagement characteristics, has a more porous soil, with less resistance and better for planting; ILPFwas characterized by a management that allowed the soil to be more resistant to the application ofloads, therefore less porous, and pasture has an intermediate behavior. Keywords: agriculturalmanagement, soil quality, ILPF, dynamic load.
Physical Indexes and surface settlement of a red oxisol indicated for different loads and types of management
Keywords: Manejos agrícolas; Solo seco; Integração Lavoura-Pecuária-Floresta (ILPF); Carga dinâmica; agricultural management; Dry soil; ILPF; Dynamic load; Latossolo vermelho; CIENCIAS AGRARIAS::ENGENHARIA AGRICOLA; OUTROS